IMPROVING TEACHER PRODUCTION METHODS FOR THE REALISATION OF VISION 2020: THE WAY FORWARD - Samaru, Lawal Garba; Abdulmalik, Idris (Sokoto Educational Review, 2020)
The paper was informed by the persistent problem of insufficient and unqualified teachers in the nation’s educational sector that has defied solution from the missionary’s time through the colonial era to post independent Nigeria. The paper discussed the qualitative and quantitative methods of teacher production and the problems associated with each and concludes that quantity should be produced without sacrificing quality so that there will be enough and qualified teachers for the realization of vision 2020. Recommendations were given in order to achieve quality in quantity, e.g. Government should introduce open and distance learning programme for massive production of teachers to cope with high demand for teachers.